Antimycobacterial dihydronaphthalenone from the endophytic fungus Nodulisporium sp. of Antidesma ghaesembilla. (September 2015) - Prabpai, Samran; Wiyakrutta, Suthep; Sriubolmas, Nongluksna; Kongsaeree, Palangpon
Graphical abstract: Highlights: The constituents of the endophytic fungus Nodulisporium sp. isolated from Antidesma ghaesembilla were investigated. Two new dihydronaphthalenones and four known compounds were isolated. The structures of the new compounds were elucidated and their antimycobacterial and antimalarial activities were evaluated. Dihydronaphthalenone2 displayed a strong antimycobacterial activity with IC50 of 3.125 μg/mL. Abstract: Two new dihydronaphthalenones (1, 2 ) with four known compounds (3 –6 ) were isolated as secondary metabolites of the endophytic fungus Nodulisporium sp. from Antidesma ghaesembilla . Their chemical structures were established based on 1D and 2D NMR spectroscopic data and HR-ESI–MS analyses. The relative configuration of2 was confirmed by single crystal X-ray crystallographic analysis. A new isofuranonaphthalenone2 displayed antimycobacterial and antimalarial activities with IC50 values of 3.125 and 11.3 μg/mL, respectively.